(untitled) (Journal of Science and Technology, 2016)
HIV is spreading and the youth bear the brunt of its onslaught. Though abstinence until marriage is thought to be the most effective method of HIV prevention for the youth, others think it is ineffective. This study assessed the feasibility of abstinence in preventing HIV/AIDS spread among tertiary students of the KNUST. Study type was non- interventional, descriptive and design current cross- sectional. Study participants were selected by stratified sampling, followed by systematic sampling. A total of 300 participants were sampled. Seventy nine (79%) (95% CI, 73.9-83.8) said STIs could be avoided by abstaining from sex. Ninety six (96%) (95% CI, 93.5-98.3%) said HIV could be acquired via sex. Ninety six (96%) (95% CI, 93.8- 98.5%) of those who said HIV could be avoided said it could be done by abstaining from sex. Seventy two (72%) were of the view that sex should start only after marriage. Sixty nine 69% (95% CI, 63.3-74.4%) said they would wait till after marriage to involve in sex. Sixty seven (67%) (95% CI, 60.7- 72.1%) were encouraged by peers to abstain from sex, Seventy four (74%) (95% CI, 68.5- 79.1%) thought colleagues their age had premarital sex and 28% (95% CI, 22.5- 33.4%) said they were pressured to have sex. Thirty one (31%) (95% CI, 25.6- 36.7%) of respondents were sexually experienced. There is the general view that HIV/AIDS spread among the youth can be reduced by abstaining from sex until marriage and that abstinence could and should be encouraged as a preventive strategy for HIV/AIDS.